SEALING OF A LAYER OF A SOUND WITH EFFECT OF ELASTIC PROPERTIES AND INHOMOGENEOUS BORDER CONDITIONS - А. Dasibekov; A.A. Yunusov; A.A. Yunusova; B.N. Korganbayev; N.A. Kuatbekov; G.A. Takibayeva; D.N. Espembetova (Academic Scientific Journal of Computer Science, 2019)
In engineering practice, the problems of compacting an earth medium of finite thickness possessing an elastic property are of great interest. In this connection, the process of one-dimensional compaction of a threephase base with a water repulsion at a depth and under the influence of an external load, depending on time and coordinate, is considered. In this case, boundary value problems for the partial differential equation are solved. Moreover, the boundary conditions are not homogeneous. Calculation formulas for calculation of pore pressure values, stresses in the skeleton of the ground and the value of precipitation for any time interval from the start of loading t have been determined. Calculations from these formulas show that the precipitation curves for inhomogeneous boundary conditions are, in their value, less than for homogeneous boundary conditions. In this case, the stresses in the skeleton of the ground for inhomogeneous boundary conditions are smaller in magnitude than for homogeneous boundary conditions and they tend to a certain asymptote